Pemanfaatan Angkutan Darat pada Distribusi Barang dari Kawasan Industri Wijayakusuma Semarang - Ursula, Lia; Rahdriawan, Mardwi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Industrial activity in Semarang growing along the north coast corridor as Wijayakusuma Industrial District along with the movement of other cities dominated modes of trucks helped shape the traffic density and increase the load on the highway. Railway container emerged as alternative modes of land transportation by utilizing a double track on the line across the north. This mode is suitable for the delivery of logistics in large-scale industry. Based on the background research is conducted with the aim to study the role of railways in the mode of distribution of logistics from the Wijayakusuma Industrial District. This research uses descriptive quantitive approach. Based on the analysis results can be concluded utilization of railway mode of container is not optimal compared with trucks. In terms of the access road to the Station Pethek not in accordance with the designation of container vehicle fully loaded. Loading and unloading facilities are still lacking to support the efficiency of the time. In terms of container train travel time is still ahead of the truck for destination Jakarta about 1-2 hours and 15-25 minutes for destination Surabaya, where the truck using the combination of toll and non toll road. But if The Trans-Java toll fully operational then trains can not compete if donâ€™t make improvement in infrastructure and operating system.Â  From the aspect of cost railway mode will be much more efficient if the cost of feeder truck can be pressed.